RELATIONSHIP BETWEEN MANUFACTURING AND MARKETING DEPARTMENTS IN SOUTH AFRICA - Boninelli, Renato Francesco (My University, 2011)
The project research investigated the inhibitors and facilitators of the relationship that exists among the marketing and the manufacturing departments in a South African manufacturing company. The increase in volume of sales due to the construction boom in local markets combined with the expansion of overseas markets, as well as a significant increase in customer demand for ‘made-toorder’ products, has placed unprecedented demand on the manufacturing and logistics functions. More importantly, the already strained relationship between manufacturing and marketing had deteriorated further, requiring some form of intervention. Functional objectives and priorities differed among the divisions and were the cause of conflicts. The aim of the research was to identify opportunities to enhance the relationship between the marketing and manufacturing departments. The research was qualitative in nature and was conducted among a sample population from marketing, manufacturing and senior management using a structured questionnaire. The results were consolidated and analysed to determine the factors. The main findings of the research were that while good communication and personal relationships contributed to the success of the relationship between marketing and manufacturing departments, the lack of common objectives and understanding of each other’s objectives, forecast accuracy and stock policies were the key factors affecting the relationship negatively. One of the key proposals presented by the participants was the need for improvements of the communication factors, although it transpired that the main factors inhibiting the relationship between marketing and manufacturing were of a structural and process nature. Improvements on the definition of aligned objectives and improvements on the level of personal relationship were also high on the list of suggestions. Recommendations based on the information gathered were offered with a view to ameliorate the relationship between marketing and manufacturing departments and hence reduce the potential for conflict and simultaneously improve the effectiveness of the organisation.
MBA - WBS
Keywords: Marketing; Manufacturing; Logistics